ECONOMIC AND POVERTY ANALYSIS IN THE TOMINI BAY AREA - Dai, Sri Indriyani S.; Akib, Fitri Hadi Yulia; Canon, Syarwani (Universitas Tidar, 2025)
Tomini Bay, as one of the largest bays in Indonesia, holds significant economic potential to drive regional economic growth. However, this potential has not yet succeeded in reducing poverty levels in the three provinces located in the Tomini Bay area, which in fact record relatively high poverty rates compared to other provinces. This study aims to analyze the influence of consumption, government expenditure, and net exports on economic growth in the Tomini Bay area and to analyze the impact of wages, education, and unemployment on poverty levels in the region. The method used is a simultaneous equations model with a Multiple Linear Regression approach using the Fixed Effect Model (FEM) on data from 2018 to 2023. The results show that, simultaneously, the variables of consumption, government expenditure, and net exports have a significant effect on economic growth, as indicated by an F-statistic value of 25.13015 and a p-value of 0.0000 (α < 0.01). In addition, the variables of wages, education, and unemployment also simultaneously have a significant effect on poverty levels, with the same F-statistic and significance values. These findings are expected to serve as a basis for policy recommendations in support of government programs aimed at promoting economic growth and reducing poverty in the Tomini Bay area.